2016
DOI: 10.1021/acschemneuro.6b00058
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Microdomains in Synapse Formation

Abstract: Membrane lipid rafts (i.e., cholesterol/sphingolipids domains) exhibit functional roles in both healthy and pathological states of the nervous system. However, due to their highly dynamic nature, it remains a challenge to characterize the fundamental aspects of lipid rafts that are important for specific neuronal processes. An experimental approach is presented here that allows for the interfacing of living neurons with an experimentally accessible model membrane where lipid order in cellular rafts can be repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Lipid rafts are important for axonal growth and guidance, most likely due to the accumulation of signalling molecules in them [ 114 ]. Some of these are the glycoprotein M6a and ephrinB receptors, which influence the neuronal cytoskeleton [ 115 , 116 ], particularly the actin network [ 11 ], and others are cell adhesion molecules and receptors for the guidance of signalling proteins (e.g., netrin-1) [ 12 , 117 ]. When an axon reaches the postsynaptic target membrane, lipid rafts provide a suitable microenvironment for the formation of a new synapse.…”
Section: Role Of Lipid Rafts In Brain Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid rafts are important for axonal growth and guidance, most likely due to the accumulation of signalling molecules in them [ 114 ]. Some of these are the glycoprotein M6a and ephrinB receptors, which influence the neuronal cytoskeleton [ 115 , 116 ], particularly the actin network [ 11 ], and others are cell adhesion molecules and receptors for the guidance of signalling proteins (e.g., netrin-1) [ 12 , 117 ]. When an axon reaches the postsynaptic target membrane, lipid rafts provide a suitable microenvironment for the formation of a new synapse.…”
Section: Role Of Lipid Rafts In Brain Developmentmentioning
confidence: 99%
“…The brain, with its complex network of neurons and glial cells, relies on the precise coordination of signalling processes for its development, and lipid rafts play a central role in this sophisticated orchestration [ 10 ]. The involvement of lipid rafts in brain development involves several fundamental processes, including neurogenesis, neuronal migration, differentiation and synaptogenesis [ 11 , 12 ]. By compartmentalising cell membranes, lipid rafts create localised environments that facilitate efficient signal transduction, which is crucial for the spatial and temporal regulation of developmental signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gopalakrishnan et al [ 141 ] demonstrated presynaptic vesicle accumulation on bilayer lipid membranes supported on silica beads (spherically supported membranes). It was later shown in vitro that the existence of lipid microdomains regulates axonal guidance to yield stable presynaptic contacts when interfaced with neurons [ 142 ]; further, it seems that specific functional groups and lateral organizations of the membrane might facilitate synaptic connections. These membrane platforms can interact with living cells and provide a means to investigate the role of membrane heterogeneity in a variety of cellular events.…”
Section: Applications Applicability and Trendsmentioning
confidence: 99%